Bone marrow-derived mesenchymal stem cells modulate BV2 microglia responses to lipopolysaccharide. - Ooi, Yin Yin; Ramasamy, Rajesh; Rahmat, Zul'Atfi; Subramaiam, Hemavathy; Tan, Shi Wei; Abdullah, Maha; Ahmad Israf, Daud; Vidyadaran, Sharmili (Elsevier, 2010)
The immunoregulatory properties of mesenchymal stem cells (MSC) have been demonstrated on a wide range of cells. Here, we describe the modulatory effects of mouse bone marrow-derived MSC on BV2 microglia proliferation rate, nitric oxide (NO) production and CD40 expression. Mouse bone marrow MSC were co-cultured with BV2 cells at various seeding density ratios and activated with lipopolysaccharide (LPS). We show that MSC exert an anti-proliferative effect on microglia and are potent producers of NO when stimulated by soluble factors released by LPS-activated BV2. MSC suppressed proliferation of both untreated and LPS-treated microglia in a dose-dependent manner, significantly reducing BV2 proliferation at seeding density ratios of 1:0.2 and 1:0.1 (p < .05). Co-culturing MSC with BV2 cells at different ratios revealed interesting dynamics in NO production. A high number of MSC significantly increases NO in co-cultures whilst a lower number reduces NO. The increased NO levels in co-cultures may be MSC-derived, as we also show that activated BV2 cells stimulate MSC to produce NO. Cell-cell interaction is not a requirement for this effect as soluble factors released by activated BV2 cells alone do stimulate MSC to produce high levels of NO. Although NO is implicated as a mediator for T cell proliferation, it does not appear to play a major role in the suppression of microglia proliferation. Additionally, MSC reduced the expression of the microglial co-stimulator molecule, CD40. Collectively, these regulatory effects of MSC on microglia offer insight into the potential moderating properties of MSC on inflammatory responses within the CNS.